V2h Charger Capable of Providing Ancillary Services - Diaz-Diaz, M (Institute of Electrical and Electronics Engineers Inc., 2023)
Residential electric-vehicle (EV) chargers are expected to become increasingly prevalent in the near future as the motivation for removing internal-combustion engines is rising. At the same time, since EVs are storage devices when parked, the possibility of using them as a backup when the grid is absent (e.g., due to failure), frequently called Vehicle-to-Home (V2H), has been gathering more attention recently. In this paper, we propose to use residential chargers not only to allow the V2H operation but also to be able to provide ancillary services to the grid when charging. In that sense, we propose to have a low-power DC charger, i.e., directly connected to the internal DC bus bypassing the on-board-charger, that can be operated in grid-feeding and grid-forming mode, depending on the grid availability. We show the requirements of the converter for a typical Chilean house, the converter topology and control design, and simulation results for both operation modes. © 2023 IEEE.